Guatones and "Chascones". Factions and Generational Units in the Christian Democracy During the Pinochet Dictatorship. (1973-1989); [“Guatones” y “Chascones”. Facciones y Unidades Generacionales en la Democracia Cristiana Durante la Dictadura de Pinochet. (1973-1989)] - Moyano-Barahona, C (Universidad de Concepcion, 2024)
This article aims to analyze the debates, tensions, and political party definitions of the Chilean Christian Democracy during the years of the Pinochet dictatorship, attending to the political practices of the party subgroups known as "guatones" and "chascones." It is proposed an approach focused on the JDC Christian Democratic Youth and the political identities that are forged in it since it is supported by a hypothesis that the subgroups analyzed have their origin in the JDC, and from there, they are projected to the party as generational politics identity units. The study is built from the analysis of party documents, press releases, and a set of in-depth interviews with Christian Democrat leaders. © 2024, Universidad de Concepcion. All rights reserved.